2010
DOI: 10.1167/iovs.09-3792
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Omega-3 Polyunsaturated Fatty Acid Supplements in Diabetic Neuropathy

Abstract: A diet balanced in long-chain PUFAs modifies retinal lipid membranes in diabetes and prevents rod dysfunction. Dietary modification was not found in the cone or glial response but a partial improvement was evident in the OPs, most likely secondary to the larger photoreceptor output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 50 publications
0
40
0
4
Order By: Relevance
“…It is likely that other metabolic abnormalities may also contribute. Alterations in timing and amplitude of the b-wave and OPs associated with diabetes have been shown to be reversible by pharmacological treatments including docosahexaenoic acid (DHA)/lutein (Arnal et al, 2009; Yee et al, 2010) and acetyl- l -carnitine (Lowitt et al, 1993). Other treatments such as lipoic acid (Johnsen-Soriano et al, 2008), topical ciliary neurotrophic factor (CNTF) (Aizu et al, 2003), propionyl- l -carnitine (Hotta et al, 1996), angiotensin-converting-enzyme (ACE) inhibition (Bui et al, 2003), protein kinase C (PKC) inhibitors (Nakamura et al, 1999), and induction of heat shock proteins (Biro et al, 1998; Nanasi & Jednakovits, 2001) have each also been shown to prevent delays and reductions in the OPs but not the b-wave.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that other metabolic abnormalities may also contribute. Alterations in timing and amplitude of the b-wave and OPs associated with diabetes have been shown to be reversible by pharmacological treatments including docosahexaenoic acid (DHA)/lutein (Arnal et al, 2009; Yee et al, 2010) and acetyl- l -carnitine (Lowitt et al, 1993). Other treatments such as lipoic acid (Johnsen-Soriano et al, 2008), topical ciliary neurotrophic factor (CNTF) (Aizu et al, 2003), propionyl- l -carnitine (Hotta et al, 1996), angiotensin-converting-enzyme (ACE) inhibition (Bui et al, 2003), protein kinase C (PKC) inhibitors (Nakamura et al, 1999), and induction of heat shock proteins (Biro et al, 1998; Nanasi & Jednakovits, 2001) have each also been shown to prevent delays and reductions in the OPs but not the b-wave.…”
Section: Discussionmentioning
confidence: 99%
“…Yee et al investigated the role for omega-3 polyunsaturated fatty acid supplements in rats with diabetic retinopathy [66]. A partial improvement was evident in the oscillatory potentials at electroretinogram, most likely secondary to the larger photoreceptor output.…”
Section: Protective Role Of Dha In the Retinamentioning
confidence: 99%
“…In this regard we have focused on examining the use of a combination of dietary supplements and drugs (enalapril, α-lipoic acid and menhaden [fish] oil) for treatment of diabetic peripheral neuropathy in rodent models (Davidson et al, 2014). The reason for selecting these three compounds is that we have demonstrated that each of these treatments individually had beneficial effects on diabetic peripheral neuropathy and each have also been shown to be safe for use in humans (Coppey et al, 2001; 2006; 2012; 2015; Davidson et al, 2011; Gopinath et al, 2012; Mcllduff and Rutkove, 2011; Papanas and Ziegler, 2014; Rudkowska, 2010; Shevalye et al, 2015; Yee et al, 2010; Ziegler et al, 2011). The primary mechanism of action of these three compounds is oxidative and inflammatory stress.…”
Section: Introductionmentioning
confidence: 99%